Therapeutic antibody glycosylation impacts antigen recognition and immunogenicity. Issue 3 (4th May 2022) - Wolf, Babette; Piksa, Mateusz; Beley, Isabelle; Patoux, Agnes; Besson, Thierry; Cordier, Valerie; Voedisch, Bernd; Schindler, Patrick; Stöllner, Daniela; Perrot, Ludovic; von Gunten, Stephan; Brees, Dominique; et al.
Abstract: In this study we show that glycosylation is relevant for immune recognition of therapeutic antibodies, and that defined glycan structures can modulate immunogenicity. Concerns regarding immunogenicity arise from the high heterogeneity in glycosylation that is difficult to control and can deviate from human glycosylation if produced in non‐human cell lines. While non‐human glycosylation is thought to cause hypersensitivity reactions and immunogenicity, less is known about effects of Fc‐associated glycan structures on immune cell responses. We postulated that glycosylation influences antigen recognition and subsequently humoral responses to therapeutic antibodies by modulating 1) recognition and uptake by dendritic cells (DCs), and 2) antigen routing, processing and presentation. Here, we compared different glycosylation variants of the antibody rituximab (RTX) in in vitro assays using human DCs and T cells as well as in in vivo studies. We found that human DCs bind and internalize unmodified RTX stronger compared to its aglycosylated form suggesting that glycosylation mediates uptake after recognition by glycan‐specific receptors. Furthermore, we show that DC‐uptake of RTX increases or decreases if glycosylation is selectively modified to recognize activating (by mannosylation) or inhibitory lectin receptors (by sialylation). Moreover, glycosylation seems to influence antigen presentation by DCs because specific glycovariants tend to induce either stronger or weaker T cell activation. Finally, we demonstrate that antibody glycosylation impacts anti‐drug antibody (ADA) responses to RTX in vivo. Hence, defined glycan structures can modulate immune recognition and alter ADA responses. Glyco‐engineering may help to decrease clinical immunogenicity and ADA‐associated adverse events such as hypersensitivity reactions. Abstract : We postulate that antibody glycosylation influences routing and processing into the endolysosome by differential receptor recognition. I: Inhibitory FcγRIIb routes the bound cargo into the early endosome (EE) where the antibody is transferred to FcRn, thus recycled back to the surface and rescued from degradation. II: Mannose recognizing lectin receptors (LRs) can route to a) the late endosome (LE) and b) destine the bound cargo to the degradative pathway (Lys: lysosome) where c) antigenic peptides are generated and presented via MHCII to T cells (T). III: Receptor‐mediated endocytosis (RME) may be inhibited if sialylated Fc N‐glycans are recognized by Siglecs.